f ( x ) is a cubic polynomial such that f ( 1 ) = 2 , f ( 2 ) = 0 , f ( 3 ) = 1 , and f ( 4 ) = 8 .
What is f ( 2 0 1 8 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I appreciate that you showed the steps. I thought solving that way would be hard, but you really made it look easy! Good job!
Log in to reply
No up-vote?
Orange:
Factor Theorem. If f ( a ) = 0 , then f ( x ) has a factor of x − a [I used h ( x − 1 ) instead of h ( x ) to get h ( 0 ) in one of the new equations later on]
h ( w ) is a quadratic since a cubic [like f ( x ) ] divided by a linear [like x − 2 ] gives a quadratic. [Also, I called the input w in the image in order not to make it seem confusing that the relation uses x-1]
Maroon:
Substitute 1, 3, and 4 for x in f ( x ) = ( x − 2 ) × h ( x − 1 ) to get more information about h [Since f ( x ) and x − 2 will equal 0 when x = 2 , we do not substitute it, since this will just give 0 = 0 and will not give any new information]. Then, because h ( 0 ) = − 2 , we know that h ( w ) = a w 2 + b w − 2 for some constants a and b .
Substitute 2 and 3 for w in h ( w ) = a w 2 + b w − 2 to get a system of linear equations in terms of a and b . Using the system, solve for a and b . We find that they both equal one-half.
Red:
Substitute the values of a and b in h ( w ) = a w 2 + b w − 2 to get the rule for h. Also, rearrange the right-hand side in order to make the rule easier to use later on. The final result is h ( w ) = 2 w ( w + 1 ) − 2
First Blue:
Substitute x = 2 0 1 8 in f ( x ) = ( x − 2 ) × h ( x − 1 ) , thus getting f ( 2 0 1 8 ) = 2 0 1 6 × h ( 2 0 1 7 )
Purple:
Substitute w = 2 0 1 7 in h ( w ) = 2 w ( w + 1 ) − 2 to get h ( 2 0 1 7 )
Second [and bigger] Blue:
Substitute the value of h ( 2 0 1 7 ) in f ( 2 0 1 8 ) = 2 0 1 6 × h ( 2 0 1 7 ) to get the final answer.
By Lagrange Interpolation, f ( x ) = − 6 2 ( x − 2 ) ( x − 3 ) ( x − 4 ) + − 2 1 ( x − 1 ) ( x − 2 ) ( x − 4 ) + 6 8 ( x − 1 ) ( x − 2 ) ( x − 3 ) = 2 1 x 3 − 2 3 x 2 − x + 4 and so f ( 2 0 1 8 ) = 4 1 0 2 8 6 4 4 1 6 .
Good job! It must've been tedious for you to expand that expression.
A cubic polynomial is in the form of f ( x ) = a x 3 + b x 2 + c x + d .
For f ( 1 ) = 2 , we have a ⋅ 1 3 + b ⋅ 1 2 + c ⋅ 1 + d = 2 or a + b + c + d = 2 .
For f ( 2 ) = 0 , we have a ⋅ 2 3 + b ⋅ 2 2 + c ⋅ 2 + d = 0 or 8 a + 4 b + 2 c + d = 0 .
For f ( 3 ) = 1 , we have a ⋅ 3 3 + b ⋅ 3 2 + c ⋅ 3 + d = 1 or 2 7 a + 9 b + 3 c + d = 1 .
For f ( 4 ) = 8 , we have a ⋅ 4 3 + b ⋅ 4 2 + c ⋅ 4 + d = 8 or 6 4 a + 1 6 b + 4 c + d = 8 .
Solving the system of equations a + b + c + d = 2 , 8 a + 4 b + 2 c + d = 0 , 2 7 a + 9 b + 3 c + d = 1 , and 6 4 a + 1 6 b + 4 c + d = 8 gives a = 2 1 , b = − 2 3 , c = − 1 , and d = 4 , so the cubic polynomial is f ( x ) = 2 1 x 3 − 2 3 x 2 − x + 4 .
Therefore, f ( 2 0 1 8 ) = 2 1 ( 2 0 1 8 ) 3 − 2 3 ( 2 0 1 8 ) 2 − ( 2 0 1 8 ) + 4 = 4 1 0 2 8 6 4 4 1 6 .
Problem Loading...
Note Loading...
Set Loading...
Let f ( x ) = a x 3 + b x 2 + c x + d . Then we have:
⎩ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎧ x = 1 : x = 2 : x = 3 : x = 4 : a + b + c + d = 2 8 a + 4 b + 2 c + d = 0 2 7 a + 9 b + 3 c + d = 1 6 4 a + 1 6 b + 4 c + d = 8 . . . ( 1 ) . . . ( 2 ) . . . ( 3 ) . . . ( 4 )
⎩ ⎪ ⎨ ⎪ ⎧ ( 2 ) − ( 1 ) : ( 3 ) − ( 2 ) : ( 4 ) − ( 3 ) : 7 a + 3 b + c = − 2 1 9 a + 5 b + c = 1 3 7 a + 7 b + c = 7 . . . ( 5 ) . . . ( 6 ) . . . ( 7 )
{ ( 6 ) − ( 5 ) : ( 7 ) − ( 6 ) : 1 2 a + 2 b = 3 1 8 a + 2 b = 6 . . . ( 8 ) . . . ( 9 )
( 9 ) − ( 8 ) : ( 8 ) : ( 5 ) : ( 1 ) : 6 a = 3 6 + 2 b = 3 2 7 − 2 9 + c = − 2 2 1 − 2 3 − 1 + d = 2 ⟹ a = 2 1 ⟹ b = − 2 3 ⟹ c = − 1 ⟹ d = 4
Therefore, f ( x ) = 2 1 x 3 − 2 3 x 2 − x + 4 and f ( 2 0 1 8 ) = 4 1 0 2 8 6 4 4 1 6 .